THE EARLY STAGES OF THE DEVELOPMENT OF MEDICAL SCIENCE IN THE TERRITORY OF UZBEKISTAN - Hakberdiev R.; Panjiyev N. B. (Web of Journals Publishing, 2025)
The first stages and State of the development of medical science on the territory of Uzbekistan, as well as the historical and cultural processes associated with it, are revealed on the basis of sources.
Keywords: Ancient Medicine, Avesto, Quran Karim, Zoroastrian, Wendidat, Saydana Fit-Tibb, Al-Qonuncha, Qorabodin, Fihrist, Epilepsy, Medical Laws.